Hydrothermal alteration mapping using ASTER data in the Infiernillo porphyry deposit, Argentina - Di Tommaso, Inés (2007)
The Infiernillo Cu-(Mo) porphyry deposit is located in the San Rafael Massif, in southern Mendoza Province, Argentina. It is hosted by and genetically related to Lower Permian Gondwanan volcanic rocks, which developed in a magmatic arc tectonic setting. The alteration zone has an oval shape about 3 km × 2 km in size, with a NNE-SSW strike. It consists of a small central quartz neck with appreciable hematite surrounded by an intense quartz-injected zone with local pervasive potassic alteration. Outwards there is a well-developed phyllic halo with intense bleaching which consists of pervasive and vein-type silicification, sericitization and pyritization. Cu and Mo anomalies are approximately coincident and are located between the silicified zone and the phyllic halo. In the outer part of the alteration zone, small polymetallic veins with pyrite, arsenopyrite, galena and minor chalcopyrite, sphalerite and electrum in quartz gangue crop out. An Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER), with three visible and near infrared (VNIR) bands, six shortwave infrared (SWIR) bands and five thermal infrared (TIR) bands, was used to characterize the Infiernillo porphyry deposit alteration area. A circular zoning pattern was clearly observed in the VNIR + SWIR band combination. Spectral analysis of the surface reflectance SWIR detected 2.20 and 2.26 μm absorptions. Field data and sample spectroscopic analyses obtained using a GER 3700 spectral radiometer and a SWIR reflectance spectrometer (Portable Infrared Mineral Analyzer PIMA) showed a good correlation with the ASTER data. The 2.20 μm absorptions, due to Al-hydroxyl, reveal the presence of clay minerals (Al-illite, kaolinite) and sericite, whereas the 2.26 μm absorption due to Fe-hydroxyl, resulted from jarosite. The field samples were also analyzed with a TIR portable spectrometer Micro-FTIR model 102. The TIR was useful for detecting surface silica and potassic alteration through analysis of five-band surface emissivity data. ASTER images provided preliminary mineralogic information and geo-referenced alteration maps at low cost and with high accuracy. In this way ASTER has been proven to be a powerful tool in the initial steps of ore deposit exploration.